Do Malaysian listed companies mitigate climate-change for tax planning? - Hui, Wei You; Rayenda Khresna Brahmana, (Penerbit Universiti Kebangsaan Malaysia, 2017)
This research aims to examine the relationship between climate-change mitigation (CCM) and tax planning in Malaysian market. 248 listed companies and employing OLS with robust standard errors from six non-financial industries were examined from 2008 to 2014. The findings indicate a significant relationship between climate-change mitigation and tax planning. Furthermore, it is observed that climate-change mitigation has contributed negatively to tax planning. It shows that companies in Malaysian market use climate change mitigation in planning their taxation matter.